WINNN Nigeria. Nutrition-sensitive kitchen garden intervention. Project profile. - International Potato Center (International Potato Center, 2020)
In the latest phase of this project, the International Potato Center (CIP) works with a range of stakeholders to improve dietary diversity and fight malnutrition by introducing biofortified orange-fleshed sweetpotato and other selected vegetables (pro Vitamin A maize, grand nuts, and moringa) as key ingredients in the diets of families with young children.